Using a 3D Printed Model as a Preoperative Tool for Pelvic Triple Osteotomy in Children: Proof of Concept and Evaluation of Geometric Accuracy. (March 2019) - Hedelin, Henrik; Swinkels, Charlotte Stor; Laine, Tero; Mack, Karsten; Lagerstrand, Kerstin
Abstract : The feasibility of 3D printing in clinical practice depends not only on the usability but also on the reliability of the method. The aims of this study were to demonstrate the feasibility of a 3D printing method for pediatric patients planned for pelvic triple osteotomy and to present a reliable quality assessment strategy for these printed models. A 10-year-old boy with Legg-Calvé-Perthes disease underwent a triple pelvic osteotomy. Preoperative and postoperative CT scans were printed as 3D models. An image-based quality assessment strategy was proposed: The printed 3D models were imaged with CT. The model images were systematically compared with the corresponding ground truth images, ie, patient images, to determine the reliability using distance measurements in the model and ground truth images. The 3D printed models were found useful in both the preoperative and postoperative stages. The models were found reliable: Strong linear correlation between the model and ground truth images both preoperatively (R = 0.99; P < 0.001) and postoperatively (R = 1.00; P < 0.001) was found. The study demonstrates the usefulness of 3D printed models in clinical practice. We also present a robust and simple strategy, using common clinical tools, to assess the reliability of 3D printed models.